Molecular Polarisabilities and Orientational Order Parameters od Binary Mesophase Mixtures of Nematic Compounds - Y. Narashima Murthy; V R Murthy (ASEAN Journal on Science and Technology for Development, 2000)
Molecular Polarisabilities and Orientational Order Parameters od Binary Mesophase Mixtures of Nematic Compounds